THE PROMOTION OF READING IN THE COMMUNITARIAN PROJECT “TOWARDS A HEALTHY USE OF THE FREE TIME”, FOR THE COMPREHENSIVE DEVELOPMENT OF THE CHILDREN IN THE FOSTER HOME “FLOWERS OF SIERRA” IN MATANZAS. - García Caballero, Ángela María; Jiménez Alonso, Mayra; Perera Hernández, Bárbara (Atenas, 2014)
In this work a system of activities for the promotion of reading with a ludic character is presented to contribute to the comprehensive formation of the children in the foster home “Flowers of Sierra” from the community “La Playa”, in the municipality of Matanzas; home conformed by children who did not have the privileged to share the reading of children books in the family bosom, and their first approximation to reading occurred in teaching spaces where the most important are formative and informative elements, obviating the ludic – aesthetic essence of reading, what frustrated the pleasure of reading in these children and readers formation.